quality of life in chemical warfare victims with ophthalmic damage\'s spouses - F. Jafari; L. Moien; M.R. Soroush; B. Mosavi (Afarand Scholarly Publishing Institute, 2011)
Background and Objective: Iraq-Iran war has been negatively affected the victims and their family members' quality of life. Especially the victims' spouses who provide care and give assistance to them who suffer from different difficulties due to living with persons with disability. The aim of this study was to assess health related quality of life in chemical warfare victims with ophthalmic damagechr('39') spouses. Materials & Methods: A group consisting of 149 female was surveyed. The 36-item short-form health survey (SF-36) questioner was used to measure quality of life. Demographic data was collected using another questionnaire. Results: the average of the chemical warfare victims with ophthalmic damagechr('39') spouses were 40.9 ± 8.48. The highest and lowest mean scores in the study population were found for physical functioning (66.5 ± 23.29) and body pain(45.78 ± 23.70) respectively. The qualities of life of the spouses were significantly lower than Iranian female normal population (p< 0.05). Unemployment other injuries in survivors were significantly accompanied with poorer health related quality of life in the spouses. Conclusion: The spouses' quality of life is negatively affected by the victims' chemical injuries. To orient the services regarding to long-term effects of chemical warfare injuries can improve the quality of life in this group. To provide better social support for the victims' spouses -as their main caregivers- can improve both the victims' and their spouses' quality of life.